The Ratio of Runx-2 and Osterix in Tension Area of Orthodontic Tooth Movements on Days 7 and 14 after Giving Mangostin - I Ketut Sudiana (Journal of Global Pharma Technology, 2019)
Background: Orthodontic relapse is the return of the tooth to the first position after being treated with an orthodontic appliance. Bone density in tension area of orthodontic in new bone formation (apposition) is critical in orthodontic treatment to prevent relapse so that orthodontic treatment can be achieved optimally through runt-related transcription factor 2 (Runx-2) and Osterix evaluation. This study aims to determine the role of Runx-2 and Osterix ratio in the tension area of orthodontic tooth movement after Mangostin administration. Material and Methods: An experimental laboratory study was conducted among 30 male Wistar rats were divided into several groups. The K1 was a negative control group (K-) without treatment, K2 was a positive control group (K +) given orthodontic mechanical strength and observed for 7 days, and K3 was a positive control group, given orthodontic mechanical strength and was observed for 14 days. In addition, K4 was a treatment group (P) given orthodontic mechanical strength and were observed for 7 days, and K5 was the treatment group (P) given orthodontic mechanical strength and were observed for 14 days. Data were tabulated and analyzed using SPSS version 17 for Windows. Results: Mangostin administration is significantly increasing the expression of Runx-2 (8.3±0.4 ng/mL), Osterix (4.7 ± 1.8 ng/mL), and bone formation (1:3.23 vs. 1:1.23) in the tension area of the treatment group (P<0.05) after 14 days. The Osterix levels were also suggest a significantly higher among groups from K1 (0.2 ± 0.2 ng/mL), K2 (1.1 ± 0.2 ng/mL), K3 (1.4 ± 0.3 ng/mL), K4 (1.3 ± 0.6 ng/mL), and K5 (4.7 ± 1.8 ng/mL) (P<0.05). The ratio of Osterix (1:3.23) seemed to be higher in treatment groups, whereas Runk2 ratio was slightly lower compared with control groups (1:1.23).Conclusion: The administration of Mangostin can increase the expression of Runx-2 and Osterix in the area tension of orthodontic tooth movement on day 14.Keywords: Mangostin, Runx-2, Osterix, Tension area, Tooth movement.